HYBRID MODEL OF PARTICIPATORY AND DELIBERATIVE E-DEMOCRACY IN INDONESIA’S ELECTIONS - Widhiarso, Dytha Ananda; Ibrahim, Ali (Informatika, Universitas Jenderal Soedirman, 2024)
E-democracy is a branch e-government that uses information technology to support the process of implementing democracy. E-Democracy itself has several models that can be applied. The election process in Indonesia itself has 2 methods, namely Noken and individual, therefore, in this research the model focused on is the hybrid of participatory and deliberative model. This research aims to see the level of public readiness in using the e-democracy model for the implementation of General Elections. The research was carried out using the literature study method with a qualitative approach and accompanied by quantitative data collection using a questionnaire. The questionnaire was used to see the level of readiness to use the e-democracy model for elections. The questionnaire uses a mixture of TAM (Technology Acceptance Model) and DOI (Divergent of Innovation) methods. The results of this research show that the range of dimension index values is above 72%, with the highest value being 82% in the Calculation Results Dimension and 80% in the Perceived Usefulness Dimension. This shows that the public is ready to use e-democracy in the election process, and increases the possibility of using e-democracy in elections.